The Effect of Temulawak and Ginger on Changes in Blood Pressure in Pregnant Women and Pain Reduction in Labouring Women in BPM Suryani North Padang Lawas Regency - Harahap, Riska Yanti; Nainggolan, Ramadhani; Tamba, Fauji Haryati (PT Inovasi Pratama Internasional, 2025)
Hypertension in pregnancy has a significant impact on maternal and fetal health. It can lead to complications such as placental abruption, organ failure, intravenous coagulation, preeclampsia, preeclampsia to become eclampsia, risk of intrauterine development, premature birth and intrauterine death. The treatment of gestational hypertension may be either pharmacological or non-pharmacological in nature. Non-pharmacological therapy for the treatment of hypertension in pregnancy may employ the use of ginger and temulawak. This study was conducted at BPM Suryani. The population comprised all pregnant women at BPM Suryani, numbering 154. The sample consisted of pregnant women with gestational hypertension, numbering 34. The recommended dose of dried temulawak and ginger is 25 grams, boiled in 200 ml of water until 100 ml of boiled water is obtained. The boiling time is 2-5 minutes. The temulawak and ginger are administered once a day for one week. At the outset of the study, the blood pressure of pregnant women with gestational hypertension was ascertained. Following the administration of temulawak and ginger, the respondents were again subjected to monitoring of their blood pressure. The data were analysed using a statistical test, namely the t-test, which is a paired sample t-test. A significant relationship was observed between systolic and diastolic blood pressure values before and after the administration of temulawak and ginger (p-value <0.05). The average difference in systolic blood pressure before and after the intervention was 5.82 mmHg with a p-value on systolic blood pressure of The p-value was 0.000 (p-value <0.05) for systolic blood pressure and 0.026 (p-value <0.05) for diastolic blood pressure. These findings suggest that the content of temulawak and ginger can be used in reducing blood pressure in pregnant women with gestational hypertension.